Analyzing the Contribution of Teacher Professional Development to Mathematics Outcomes: A Ghanaian Perspective from TIMSS 2022 - Baah, Doris; Yunus, Hissan; Štrok, Andreja Vlahek (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates the relationship between Teacher Professional Development (TPD) and Mathematics Achievement (MA) using data from the 2022 Trends in International Mathematics and Science Study (TIMSS) for Ghana. Methodology: Using a quantitative approach, data were collected from 200 teachers engaged in professional development programs through a structured questionnaire. The analysis SEMPLS for relationships observed between teacher development and mathematics achievement. Main Findings: Results indicate a significant positive correlation between TPD and MA, with a path coefficient of 0.329 (p = 0.026), suggesting that professional development contributes to improved student achievement. Additionally, a reciprocal relationship was observed, where higher MA also encouraged increased teacher development (coefficient 0.346, p = 0.046), highlighting a bidirectional influence. The findings align with previous research indicating that professional development enhances teaching quality and, in turn, student outcomes. Novelty/Originality of this study: The novelty of this research lies in its focus on Ghana, where the impact of TPD on mathematics achievement has not been extensively explored within the context of international assessments. The practical implications suggest that Ghana should continue to prioritize sustainable, evidence-based professional development initiatives that foster teacher reflection and improve pedagogical practices. However, limitations such as the sample size and the contextual focus on Ghana warrant caution in generalizing the findings. Future research should expand to include additional contextual factors and a broader range of educational settings to further explore the complex dynamics of teacher development and student achievement in mathematics.